Maternal death due to COVID-19: is there anything that changed during the treatment? A case report - Pınar Kumru; Ebru Çöğendez; Eralp Bulutlar; Fırat Ortak; Neslihan Başkılıç Tülin Yollu; Resul Karakuş Semra Kayata&#351 (Perinatal Medicine Foundation, 2021)
Objective We present a case of maternal death due to COVID-19 and aimed to review our COVID-19 management strategies during pregnancy and changing strategies at different times of the epidemic through the present case. Case(s) Our patient was 35 years old, gravida 2, parity 1, 28 weeks pregnant, who admitted to the emergency service of our hospital for the first time with the complaints of severe dry cough, respiratory distress, fever, abdominal pain and vomiting, with suspected COVID-19. She was admitted to the delivery room. As the oxygen need increased within hours and the oxygen saturation decreased to 60%, the patient was intubated 21 hours after hospitalization and was admitted to our second level adult intensive care unit. Due to the development of fetal distress 1 hour after intubation, the patient was taken to emergency cesarean section. Four days after the operation, the patient died due to cardiopulmonary arrest in the 3rd level intensive care unit of the hospital where she was transferred. Conclusion This report demonstrates that COVID-19 can be severe in a pregnant woman, that the importance of early diagnosis and treatment, the difficulties of clinical management in case of progression of the disease, and ultimately, the maternal and neonatal consequences can be devastating.